Cognitive Biases in Performance Appraisal: Experimental Evidence on Anchoring and Halo Effects With Public Sector Managers and Employees - Belle, Nicola; Cantarelli, Paola; Belardinelli, Paolo (Review of public personnel administration, 2017)
A systematic literature review of performance appraisal in a selection of public administration journals revealed a lack of investigations on the cognitive biases that affect raters’ evaluation of ratees’ performance. To address this gap, we conducted two artefactual field experiments on a sample of 600 public sector managers and employees. Results show that anchoring and halo effects systematically biased performance ratings. For the former, average scores were higher when subjects were exposed to a high rather than a low anchor. For the latter, higher ability on one performance dimension led participants to provide a higher average score on another performance dimension. Halo effect was moderated by rater’s gender. We conclude by discussing the study limitations and providing suggestions for future work in this area.